Maldives : Identifying Opportunities and Constraints to Ending Poverty and Promoting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2015)
Maldives is an island nation scattered in the Indian Ocean comprising 1,190 small coral islands of which 190 are inhabited by a local population of 341,000. Maldives’ unique archipelagic coral island provides the country with an extremely rich and diverse marine ecological system. With more territorial sea than land, marine resources have played a vital role shaping the contours of economic development, with nature-based tourism being the key driver of economic growth and fisheries an important sector of employment for the local population. Maldives developed a successful high-end tourism sector, whose sizeable rents have been redistributed to the population to address its development challenges. This systematic country diagnostic for Maldives aims at identifying the most critical constraints and opportunities facing the country as it works towards promoting sustainable growth, reducing poverty and boosting shared prosperity. In addition to serving as a public good for the government, civil society, research and academic community, and local and international development partners, the findings of the SCD will be used as key inputs in the preparation of the WBG strategy, the Country Partnership Framework, which will outline how the Bank Group’s engagement in Maldives can best contribute towards achieving the twin goals.